Bacterial Quorum-Quenching Lactonase Hydrolyzes Fungal Mycotoxin and Reduces Pathogenicity of Penicillium expansum—Suggesting a Mechanism of Bacterial Antagonism - Shlomit Dor; Dov Prusky; Livnat Afriat-Jurnou (Journal of Fungi, 2021)
Penicillium expansum is a necrotrophic wound fungal pathogen that secrets virulence factors to kill host cells including cell wall degrading enzymes (CWDEs), proteases, and mycotoxins such as patulin. During the interaction between P. expansum and its fruit host, these virulence factors are strictly modulated by intrinsic regulators and extrinsic environmental factors. In recent years, there has been a rapid increase in research on the molecular mechanisms of pathogenicity in P. expansum; however, less is known regarding the bacteria–fungal communication in the fruit environment that may affect pathogenicity. Many bacterial species use quorum-sensing (QS), a population density-dependent regulatory mechanism, to modulate the secretion of quorum-sensing signaling molecules (QSMs) as a method to control pathogenicity. N-acyl homoserine lactones (AHLs) are Gram-negative QSMs. Therefore, QS is considered an antivirulence target, and enzymes degrading these QSMs, named quorum-quenching enzymes, have potential antimicrobial properties. Here, we demonstrate that a bacterial AHL lactonase can also efficiently degrade a fungal mycotoxin. The mycotoxin is a lactone, patulin secreted by fungi such as P. expansum. The bacterial lactonase hydrolyzed patulin at high catalytic efficiency, with a kcat value of 0.724 ± 0.077 s−1 and KM value of 116 ± 33.98 μM. The calculated specific activity (kcat/KM) showed a value of 6.21 × 103 s−1M−1. While the incubation of P. expansum spores with the purified lactonase did not inhibit spore germination, it inhibited colonization by the pathogen in apples. Furthermore, adding the purified enzyme to P. expansum culture before infecting apples resulted in reduced expression of genes involved in patulin biosynthesis and fungal cell wall biosynthesis. Some AHL-secreting bacteria also express AHL lactonase. Here, phylogenetic and structural analysis was used to identify putative lactonase in P. expansum. Furthermore, following recombinant expression and purification of the newly identified fungal enzyme, its activity with patulin was verified. These results indicate a possible role for patulin and lactonases in inter-kingdom communication between fungi and bacteria involved in fungal colonization and antagonism and suggest that QQ lactonases can be used as potential antifungal post-harvest treatment.